Arbitrations and Appraisals in the Missouri Courts - George Williams Foster Jr. (Washington University Law Quarterly, 1954)
A survey of court opinions dealing with arbitration matters is primarily a study of breakdowns, real or alleged, in the arbitral arrangement. Such a study of appellate opinions necessarily presents a somewhat warped picture of Missouri arbitration because the emphasis is almost entirely upon the pitfalls of common-law or statutory rules relating to arbitration, or upon the failure of the parties or the arbitrators to abide those rules. Almost no emphasis is placed upon arbitrations which do work, quietly and efficiently, and are accepted by the parties.
Keywords: Arbitration and award